PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MOTIVASI BELAJAR KIMIA PESERTA DIDIK KELAS XII-C1 SMA NEGERI 11 SEMARANG - Nabila, Farah; Maharani, Endang T.; Hendrawati, Tuti (Journal of Lesson Study in Teacher Education, 2025)
Based on the results of observations conducted at SMA Negeri 11 Semarang, especially in class XII-C1, it appears that students' learning motivation in chemistry is still low. This is because teachers still apply conventional learning. Teachers often use lecture methods and dominate learning so that students are more often used as learning objects than learning subjects. The right solution to this problem is to apply the Teams Games Tournament (TGT) type cooperative learning model. This study aims to describe the increase in teacher activity and increase in student learning motivation by applying the Teams Games Tournament (TGT) type cooperative learning model. This study uses a quantitative descriptive research method. The subjects in this study were 36 students of class XII-C1 of SMA Negeri 11 Semarang. Data collection used the observation method. Teacher activity increased with an average score of 77.5% in cycle I and 92.5% in cycle II. Student activity or student learning motivation during the learning process with an average score in cycle I of 62% and cycle II of 88.5%. From these results, it can be concluded that the cooperative learning model of the Teams Games Tournament (TGT) type can increase the motivation to learn chemistry of class XII-C1 students of SMA Negeri 11 Semarang.